Lutheran Theological Education in an Ecumenical and Multicultural Setting: Public Use of Archives and Perceptions at the Lutheran Theological Institution (LTI) Library, Pietermaritzburg, South Africa (Atlanti, 2016)
This paper reports on the findings of a study that was carried out in 2014 at the Lutheran Theological Institute (LTI) Library on public use of archives and user perceptions about archives in the library. Archival registration data in the form of user statics, library membership statistics, annual reports and a questionnaire were the primary sources of data. The study established that users were generally aware of what archives are, that the most consulted archival material were church and diocese minutes and that amongst the recommended strategies to promote visibility for the archives were exhibitions, guided tours, publications, an open day on archives and the establishment of a friends of the archives group.
Keywords: Exhibitions; publications; outreach; ICA Archives Day; LTI Library